How the need for cognition influences film viewing intentions through narrative transportation: the moderating role of emotional contagion in short-video marketing - Liu, Lei; Deng, Wengen (Frontiers in Communication, 2025)
This study investigates how individual cognitive and affective traits shape viewers’ intentions to watch films promoted through short-video platforms. Drawing on narrative transportation theory and the Extended Transportation-Imagery Model, we propose that need for cognition influences viewing intention directly and indirectly through narrative transportation, with emotional contagion moderating this indirect pathway. Data were collected from 362 Chinese users of Douyin and Kwai through an online survey and analyzed using structural equation modeling. The results show that individuals with higher need for cognition experience stronger narrative transportation and demonstrate higher intention to watch the promoted film. Narrative transportation serves as a significant mediator, revealing its central role in translating cognitive engagement into behavioral intention. Emotional contagion further strengthens the relationship between narrative transportation and intention, indicating that viewers who are more susceptible to emotional synchrony are more likely to convert immersive experiences into action. These findings extend narrative persuasion theory to short-form media and highlight the joint contributions of cognition and emotion in digital film marketing. The study offers practical implications for audience segmentation and the design of personalized promotional content on short-video platforms.